Attitudes of the english language university instructors towards the use of technology in teaching and learning - Vahid Motamedi (Journal of Education and Learning (EduLearn), 2020)
The outburst of information technology in the later parts of the twentieth century has taken the whole world into its scope. There is an ever growing use of computers in the workplaces and universities. The purpose of this study was to measure the attitudes of the English language university instructors towards the use of computers. It was a descriptive study and data was collected by a survey. This study’s population consisted of two hundred university instructors equally divided into male and female. These instructors were randomly selected from different universities. The findings revealed that there was a significant difference between the views of the males and females instructors. Moreover, those who had no professional qualification had the highest mean score. The English language university instructors should be trained in the use of computers so that they might be able to use them more effectively in classroom settings.